P122 The SIMPLE community pharmacy service for the management of COPD. (December 2018) - Murphy, AC; Goodyear, LI
Abstract : Background: SIMPLE intervention, is an acronym for Stop Smoking, Inhaler technique, Monitoring, Pharmacotherapy, Lifestyle and Education. 1 The impact of community pharmacists undertaking a COPD service based on the SIMPLE has not been evaluated to date. Some initial findings from the service evaluation are presented focusing on improvements in patient's metered dose inhaler (MDI) technique. Method: The initiative was delivered through 55 community pharmacies nationally. Community pharmacists trained in the SIMPLE intervention delivered the service. Baseline data were obtained on inhaler technique using a '7-steps' scoring system, and on COPD control (COPD assessment test (CAT)) and breathlessness (MRC dyspnoea score). Further demographics and outcomes were recorded but not reported here. Subjects were followed up 2 months and 6 months post consultation. Inhaler technique was reassessed at 2 months. Results: 125 participants were included at baseline; 55 lost to follow-up at six-months. Total CAT scores reduced by 3.6 points over this six-month period (p<0.001), MRC dyspnoea score at 6 months was 2.60 (95% CI 2.35, 2.85) compared with 2.80 (95% CI, 2.58, 3.02) at baseline (p=0.007). 60 participants were using a MDI at baseline. For steps 1–4 and 7 there was no difference to the percentage of correct use at baseline and 2 months. For the two steps of breathing in with the correct inspiratory flow and holding the breath post inhalation performance significantly improved; inspiratory flow 39% v74% and holding breath 54% v 82% (p<0.001). Discussion: The improvement in inhaler technique is likely to have contributed to the improved CAT and dyspnoea scores. Further analysis is required to confirm the nature of any such relationship. In this initial analysis of the service there is strong evidence that the SIMPLE intervention implemented by community pharmacists can improve inhaler technique. Reference: SIMPLE approach to asthma management . http://www.tin.nhs.uk/innovation-nhs-east-midlands/innovation-in-practice/regional-innovation-fund-projects-2009–10/simple-approach-to-asthma-management/